Membingkai Kasih Ibu Lewat Diksi: Studi Semantik dan Emosi dalam Lirik Lagu Ina’ (Ibu) Karya Apang - Hermansyah, Wawan (Ruang Kata, 2025)
This study aims to examine the semantic meanings and emotional content embedded in the lyrics of Ina’, a traditional song by Apang from Sumbawa, which centers the figure of a mother as the embodiment of love and sacrifice. Unlike previous studies that rarely combine semantic and emotional analysis within the context of Sumbawan folk songs, this research applies a lexical semantic approach and emotion analysis grounded in cultural linguistics to explore how word choices convey deep affective, spiritual, and social values. The study employs a qualitative-descriptive method, collecting data through lyric documentation, observations of local cultural contexts, and semi-structured interviews with native speakers and cultural practitioners. Data were analyzed by identifying denotative and connotative meanings, as well as interpreting emerging emotional themes. The findings reveal that the lyrics of Ina’ contain positively connoted expressions that evoke empathy, gratitude, and respect toward the mother figure. This highlights that language in traditional music serves not only as an aesthetic medium but also as a means of transmitting familial and spiritual values deeply rooted in Sumbawan culture. The implications of this research are expected to enrich cultural linguistic and semantic studies based on local wisdom, while also supporting efforts to preserve oral literature through scholarly approaches